Assessment of Mortality Risk Factors in Patients with Severe COVID-19 Acute Respiratory Distress Syndrome - Alizamin Sadigov; Malahat Sultanova; Emil Gasimov; Gunel Sadigova; Sharaf Huseynova; Cavid Pashayev (New Advances in Medicine and Medical Science Vol. 6, 2023)
The aim of this study was to identify risk factors predicting mortality in patients with severe COVID-19 complicated with ARDS. We specifically tested the association of these clinical outcomes with the changes in PaO2/FiO2 ratio (P/F), arterial blood pH the consolidation to ground glass opacities ratio (C/ GGO) the Murray lung injury score (MLIS). COVID-19 disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which originated in China, has caused a global outbreak that has affected more than 70 million people worldwide. . The clinical characteristics of COVID-19 survivors and non-survivors ARDS groups were compared clinically, laboratory, and radiographically. Results indicated that the median age of non-survivors ARDS patients was 68.4 years old, which was significantly older than those with survivors ARDS by 9,9 years. Male and patients with BMI>30 were more likely to die from ARDS. The prevalence of consolidation (Consolidationglass opacities ratio>1) in lung, secondary bacterial infection, mechanical ventilation and pack of use dexamethasone before intubation were common among non-survivors ARDS. The values of assessing scores (MLIS, Cons/GGO ratio, P/F ratio and SOFA) were changed differently. Among non-survivor group these scores were getting worsening by time, and in contrary to these among survivor all these scores were getting better and to the end of the 16-th were near normal ranges. Partial pressure of oxygen to fraction of inspired oxygen (PaO2/FiO2) at the time of admission also was significantly lower compared to survivors ARDS patients (p<0.05) and arterial blood gas analysis values were significantly differ: partial pressure of carbon dioxide (PaCO2) was markedly higher (p=0.023), PaO2 was lower (p=0.026) and acidity of the blood pH was also lower (p=0.02). We discovered risk factors for death in ARDS patients with severe COVID-19. The clinical outcomes of patients with severe COVID-19 complicated by ARDS may be impacted by the healthcare providers’ use of these findings.